Pariwisata Berbasis Masyarakat Untuk Menunjang Pariwisata Berkelanjutan Di Desa Wisata Kaki Langit, Bantul, DI Yogyakarta - Rahman, Firly; Sunarta, I Nyoman; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i01.p06, 2023)
Community based tourism can be defined as the concept of sustainable tourism development. Local community participation is the main focus in the concept of community based tourism, so that it can have a positive impact in the social, cultural, economic and environmental fields. The Kaki Langit Tourism Village is one of the tourist villages which is becoming a trend in the province of Yogyakarta, therefore this research was conducted to identify forms of local community participation so that it can become an example and inspiration for other tourist villages in Indonesia. This research uses qualitative data types. The data sources used are primary and secondary. Data collection techniques in this research were observation, in depth interviews and documentation. The data analysis technique used is descriptive qualitative through three activities, namely data reduction, triangulation, and drawing conclusions. The results of this research indicate that thanks to tourism activities in the Kaki Langit Tourism Village which was formerly one of the poorest villages in Yogyakarta province but currently the welfare of local communities has increased, this research also shows forms of local community participation, as well as alternative strategies for community based sustainable development. Keywords: Tousim Village, Community Based Tourism, Sustainable Tourism, Local Community Participation